2021
DOI: 10.3389/fmicb.2021.641141
|View full text |Cite
|
Sign up to set email alerts
|

Gut Structure and Microbial Communities in Sirex noctilio (Hymenoptera: Siricidae) and Their Predicted Contribution to Larval Nutrition

Abstract: The European woodwasp, Sirex noctilio Fabricius, is a major invasive quarantine pest that attacks and kills pine trees outside of its native range. Insect gut structure and gut microbiota play crucial roles in various life activities. Despite a few reports in nutrition and survival, an extensive study on the S. noctilio larval gut microbiome is lacking. We studied the gut structure using a stereo microscope and used high throughput sequencing of the bacterial 16S rRNA genes and fungal internal transcribed spac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 72 publications
1
23
0
Order By: Relevance
“…The bubble diagram of pathway enrichment analysis was made using the R package "ggplot2." The R version was 4.0.2, and R packages were described previously (Chen and Boutros, 2011;Li et al, 2021). Significance was declared at P < 0.05.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The bubble diagram of pathway enrichment analysis was made using the R package "ggplot2." The R version was 4.0.2, and R packages were described previously (Chen and Boutros, 2011;Li et al, 2021). Significance was declared at P < 0.05.…”
Section: Discussionmentioning
confidence: 99%
“…Only those taxa with an abundance >1% of the total community in at least one treatment were included. The Venn diagram was analyzed using the R package “VennDiagram.” Pearson’s correlation analysis was carried out by R package “ggplot2,” “corrplot,” and “pheatmap.” The bubble diagram of pathway enrichment analysis was made using the R package “ggplot2.” The R version was 4.0.2, and R packages were described previously ( Chen and Boutros, 2011 ; Li et al, 2021 ). Significance was declared at P < 0.05.…”
Section: Methodsmentioning
confidence: 99%
“…It is possible that Enhydrobacter is common to Ecdysozoan microbiomes, as it is also an abundant taxon in the gut contents of larval wood wasps (J. Li et al 2021) and nematodes (Adam et al 2014). Members of Enterobacteriaceae included OTUs 2 and 20.…”
Section: Tardigrade-associated Taxamentioning
confidence: 99%
“…Some evidence has suggested that the gut bacterial community has a significant impact on the host's digestion, nutritional acquisition, and juvenile development [8], which are often linked to the overall community structure [9][10][11]. Previous studies have examined both gut bacterial diversity and biological functions in a wide range of arthropods [12][13][14], demonstrating the critical role of the bacterial community found in arthropod guts [15][16][17].…”
Section: Introductionmentioning
confidence: 99%